Desemaranhamento de Qutrits - Breno Marques Goncalves Teixeira (2009)
The interaction of entanglement system with the enviroment tends to degrade the entanglement. It has been shown that, for 2 . 2 system (two qubits) interacting with spontaneus emission reservoir there are essentially two types of dynamics: sudden death and asymptotic decayof entanglement [1]. The entanglement behavior for bibartite systems of higher dimension interacting with the enviroment has also been subject of some studies. Lastra et. al. [2] showed that, in system higher dimension, the disentanglement dynamics may present abrupt changes, along with sudden death. In this work we study quantum system of two qutrits that interact with the enviroment indenpendly, and how the entanglement evolution of these systems changes for different internallevel configuration of each subsystem. Therefore, we use Negativity [3] as an entanglement quantifier that gives information on free entanglement (distillable) [4], which is important to quantum information protocols [5]. The dynamics calculation is done using Quantum Trajectories Method [6, 7],with allow us to computationally simulate quantum system. This method is equivalent to solving the Master Equation [6, 8] and is related to experiments in wich information on the system is obtained by monitoring the reservoir.